2007
DOI: 10.1007/s00134-007-0860-3
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal permeability increasing protein gene variants in children with sepsis

Abstract: BPI Taq gene polymorphism is the accurate predictor of the severity of sepsis in children admitted to the PICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Haplotype analysis of rs2234237and rs2234246 in patients with septic shock and control subjects and in the survivors and non-survivors clinical course of severe sepsis. [16][17][18][19][20] It is anticipated that these fi ndings will lead to the use of new diagnostic markers, prognostic indicators, and therapeutic strategies for sepsis. [29] In this study, two common SNPs in the TREM-1 gene were evaluated with regard to the susceptibility and prognosis of septic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haplotype analysis of rs2234237and rs2234246 in patients with septic shock and control subjects and in the survivors and non-survivors clinical course of severe sepsis. [16][17][18][19][20] It is anticipated that these fi ndings will lead to the use of new diagnostic markers, prognostic indicators, and therapeutic strategies for sepsis. [29] In this study, two common SNPs in the TREM-1 gene were evaluated with regard to the susceptibility and prognosis of septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Studies [16][17][18][19][20] confirmed that single nucleotide polymorphisms (SNPs) in some particular genes, such as interleukin-6 gene polymorphisms G-174>C and G-572>C, bactericidal permeability increasing protein (BPI) (G545>C) Taq and BPI (A645>G) 216, β-defensin 1 variant haplotype -20G/-44G/-52G, IRAK-1 variant haplotype, protein C-1641 AA genotype, etc, play a critical role in severe sepsis or septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, SNPs in the genes participating in the pathophysiologic process of sepsis may contribute to the susceptibility to and outcome of sepsis [19,20]. Recent studies have identified that IL-6 Ϫ174G/C and Ϫ572G/C, bactericidal permeability increasing (BPI) protein gene Taq polymorphism, human ␤-defensin 1 gene (DEFB1) Ϫ44G/C, and protein C Ϫ1641AA genotype, as well as IL-1 receptor-associated kinase (IRAK-1) haplotype, were associated with the clinical course of severe sepsis [21][22][23][24][25]. It is anticipated that these findings will lead to new diagnostic markers and prognostic indicators as well as therapeutic strategies for sepsis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is a complex disease resulting from the interactions between environmental factors and genetic factors (Cohen 2002;Stuber 2001). It has been anticipated that single nucleotide polymorphisms (SNPs) in genes participating in pathophysiologic process of sepsis may contribute to the susceptibility to sepsis and the outcome of sepsis (Arcaroli et al 2006;Chen et al 2007;Cobb and O'Keefe 2004;Lin and Albertson 2004;Michalek et al 2007;Pinsky 2007;Stuber 2001;Walley and Russell 2007), and genetic study in sepsis will lead to new diagnostic markers and prognostic indicators as well as therapeutic strategies for sepsis (Cobb and O'Keefe 2004).…”
Section: Introductionmentioning
confidence: 99%